2021
DOI: 10.1159/000518560
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Outcomes of Holmium Laser Enucleation of the Prostate: A Systematic Review

Abstract: <b><i>Introduction:</i></b> The aim of the study was to systematically review the literature and describe perioperative complications of holmium laser enucleation of the prostate (HoLEP), including the Clavien-Dindo classification of surgical complications. <b><i>Methods:</i></b> All English language publications on HoLEP were evaluated. We followed the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) guidelines to evaluate PubMed<sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
(107 reference statements)
0
5
0
1
Order By: Relevance
“…PPUI, a common complication in BPH patients who have received TURP or HoLEP and other laser techniques, is usually caused by damage to the proximal part of the rhabdosphincter, distal to the seminal colliculus 9 , 42 . The incidence rate of PPUI in BPH is 1.8–8.8%, the prevalence rate of transient PPUI, which resolves within 1 year is 7%, and the incidence rate of permanent PPUI is 1.3% 13 , 43 . Several studies have reported the prevalence of PPUI in patients with PCa as 4–30%, according to the definition of PPUI used 44 .…”
Section: Discussionmentioning
confidence: 99%
“…PPUI, a common complication in BPH patients who have received TURP or HoLEP and other laser techniques, is usually caused by damage to the proximal part of the rhabdosphincter, distal to the seminal colliculus 9 , 42 . The incidence rate of PPUI in BPH is 1.8–8.8%, the prevalence rate of transient PPUI, which resolves within 1 year is 7%, and the incidence rate of permanent PPUI is 1.3% 13 , 43 . Several studies have reported the prevalence of PPUI in patients with PCa as 4–30%, according to the definition of PPUI used 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We could speculate that laser setting is likely to play a key role in addressing functional outcomes but other elements are probably more critical. In particular, maintaining an anatomical dissection plane, reducing traction to the sphincter during the enucleation and avoiding capsular perforation are together crucial to allow a fast recover from irritative symptoms following HoLEP ( 30 ). Recent evidence also demonstrated the importance of the apical release in the very beginning of the procedure to maximize functional success ( 18 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%